2001
DOI: 10.2113/gscanmin.39.5.1405
|View full text |Cite
|
Sign up to set email alerts
|

The Melilite-Bearing High-Temperature Skarns of the Apuseni Mountains, Carpathians, Romania

Abstract: The melilite-bearing skarns of Cornet Hill (CH) and Upper Cerboaia Valley (UCV), in the Apuseni Mountains of Romania, occur at the contact between monzodiorite bodies of Ypresian age (Paleocene) and Neojurassic calcitic marbles. Typical wollastonite -grossular -diopside endoskarns are separated from exoskarns (tilleyite and spurrite or wollastonite at CH, wollastonite only at UCV), at most places, by a melilite-rich rock, in which veins and vein-like zones of recrystallization are composed only of idiomorphic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…The presence of silica in apatite seems to be real as the analysis of apatite included in pyrrhotite reveals 8% SiO 2 and only 0.3% Al 2 O 3 . The presence of silica in apatite is a typical feature of carbonate-rich magmatic rocks (Rønsbo 1989) and skarns (Pascal et al 2001). …”
Section: Phosphatesmentioning
confidence: 99%
“…The presence of silica in apatite seems to be real as the analysis of apatite included in pyrrhotite reveals 8% SiO 2 and only 0.3% Al 2 O 3 . The presence of silica in apatite is a typical feature of carbonate-rich magmatic rocks (Rønsbo 1989) and skarns (Pascal et al 2001). …”
Section: Phosphatesmentioning
confidence: 99%
“…Spurrite occurs characteristically in skarns formed during the shallow intrusion of igneous rock into limestone in USA (Tilley, 1929;Joesten, 1976), Mexico (Wright, 1908), Russia Galuskina et al, 2009) and Canada (Rosa and Martin, 2010); and it was also found in the pyrometamorphic rocks of Hatrurim Formation in Israel where the combustion of organic fossil fuel provided a heat source (Sokol et al, 2008). Tilleyite was initially discovered in thermally metamorphosed limestones from a contact zone in California, USA (Larsen and Dunham, 1933), and later confirmed to abound in the high-temperature skarn in Cornet Hill in Romania Pascal et al, 2001;Grice, 2005), where spurrite was occasionally found in association. Galuskinite is a newly discovered mineral found in altered silicatecarbonate xenoliths a few meters in diameter in the Birkhin gabbro massif of Russia.…”
Section: Introductionmentioning
confidence: 99%
“…The petrogenetic grids used to deduce the observed assemblages were explained using reactions involving quartz, calcite and the minerals in the sequence. However, at Fuka (and elsewhere in Apuseni mountains, Pascal et al, 2001;Marincea et al, 2001) mineralogy and textural features of the skarn does not suggest a progressive sequence of reactions involving quartz. The formation of spurrite and tilleyite is suggestive of its formation with out early wollastonite.…”
Section: Petrogenetic Grids and Its Implicationsmentioning
confidence: 85%
“…High temperature conditions for spurrite and gehlenite skarn formation have been reported elsewhere as well. In a recent study on the formation of spurrite and gehlenite bearing skarn in Apuseni Mountains, Romania, Pascal et al (2001) reported temperature conditions of around 750°C at 750 bars and a maximum concentration of silica of 2.9 ×10 −4 m. Their study also indicated that the variation of CO 2 in the fluid is controlled by the activity of silica, since CO 2 is produced during the formation of spurrite, which in turn needs silica in the fluid to react with the calcite. Our results are also in agreement with this, however the skarn formation at Fuka occurred at a higher temperature condition that those in Apuseni.…”
Section: Petrogenetic Grids and Its Implicationsmentioning
confidence: 99%